Effects of Shexiang Baoxin Pill for Coronary Microvascular Function: A Systematic Review and Meta-Analysis - Wang, Mengxi; Shan, Yiwen; Sun, Weixin; Han, Jie; Tong, Huaqin; Fan, Manlu; Chen, Jiandong; Yu, Peng; Shen, Le; Chen, Xiaohu (Frontiers in Pharmacology, 2021)
Background: The coronary microvascular dysfunction has attracted more and more attention in recent years, but there is still a lack of effective treatment. Shexiang Baoxin Pill is one of the commonly used drugs for the treatment of coronary artery disease in China. More recently, some studies found that it has the effect of improving coronary microvascular function. Objective: To evaluate the effects of Shexiang Baoxin Pill for coronary microvascular function. Methods: Databases including MEDLINE, Web of Science, CNKI, Wanfang, The Cochrane Library, EMbase, VIP and CBM were searched from inception to June 2021 to screen out relevant clinical studies. The 2019 version 2 of the Cochrane risk of bias tool (RoB2) were used to assess the methodological quality of the included studies. RevMan 5.3 software was used for meta-analysis. Results: Eleven studies meeting the criteria were included, with a total of 1075 patients. The results of meta-analysis showed that compared with conventional treatment alone, combination of Shexiang Baoxin Pill and conventional treatment can further increase the coronary flow reserve (CFR) [mean difference (MD)=0.43, 95%CI (0.28, 0.58), P<0.000 01], decrease the index of microvascular resistance (IMR) [MD=-4.23, 95%CI (-5.49, -2.97), P<0.000 01], increase serum nitric oxide (NO) [MD=11.96, 95%CI (2.74, 21.18), P=0.001] and decrease serum hypersensitive C-reactive protein (hs-CRP) [MD=-2.49, 95%CI (-3.08, -1.90), P<0.000 01], but did not increase the time of duration on the exercise testing (TET) [MD=3.64, 95%CI (-1.17, 8.45), P=0.14]. In terms of safety, a total of 10 patients developed adverse reactions in the intervention group and 17 patients developed adverse reactions in the control group. Conclusion: Current evidence suggests that Shexiang Baoxin Pill may be effective in the improvement of coronary microvascular function when used in combination with conventional treatment. However, due to the low quality of the included studies, lack of placebo control and high heterogeneity among different studies, we should take a cautious attitude towards this conclusion. Moreover, the safety of Shexiang Baoxin Pill remains uncertain, more high-quality clinical studies are needed to verify the efficacy and safety of this drug in the future.